Characterization and proposal for the post-harvest management of Byrsonima crassifolia L. fruits, yellow and red phenotypes - Rivas-Robles, Emanuel; Vargas-Ortiz, Manuel Alejandro; Vela-Gutiérrez, Gilber; Caballero-Roque, Adriana; Quintana-Obregón, Eber (Comunicata Scientiae, 2025)
Nanche is a native fruit with high nutritional and functional value; however, its commercialization is hindered by its short post-harvest shelf life. This study evaluated the physical traits, chemical composition, bioactive compounds, and postharvest management of mature yellow and red nanche fruits collected in Chiapas, Mexico. Standard AOAC methods were employed to evaluate physicochemical parameters, while antioxidant capacity, total polyphenols, flavonoids, and chlorogenic acid were quantified using spectrophotometric assays. To enhance preservation, methyl jasmonate (MeJA) was applied under varying temperature conditions. Both phenotypes showed comparable nutritional potential; however, the red nanche exhibited a lower moisture content, higher levels of antioxidant compounds, and better postharvest performance following MeJA treatment. The combination of MeJA and refrigeration effectively extended shelf life and improved fruit quality, offering a viable strategy to strengthen the nanche value chain and promote its market integration as a functional bioresource.